Peningkatan Kematangan Manajemen Proyek menggunakan Kerangka Kerja KPMMM: Studi Kasus Perusahaan Konsultan Teknologi Informasi PQR - 'ilma Insyifani, Izza; Raharjo, Teguh; K. Budiardjo, Eko; Mahatma, Kodrat (Technomedia Journal, 2023)
An information technology solution company, PQR, runs project-based businesses managed by Program Management Office (PMO) department. PQR project completion implementation hasn't met 95% timeliness target, PMO noted 12 out of 14 projects in 2019-2021 were finished late. To minimize potential business losses, companies need to improve project management implementation, starting with PMO project management maturity analysis. Based on its maturity, recommendations for project management implementation improvement can be formulated in directed manner. This study measures the project management maturity level using Kerzner Project Management Maturity Model (KPMMM), which refers to Project Management Body of Knowledge (PMBOK). Maturity analysis performed quantitatively using KPMMM questionnaire, and improvement recommendations were compiled qualitatively using maturity analysis result mapping to PMBOK theory. Result stated that PQR was at maturity level one, Common Language, out of five levels. Recommended improvement is applying principles of PMBOK process through each phase of project management related to KPMMM knowledge category. In addition, training is also recommended for PMO PQR project managers regarding achieving level one criteria that are below target. By implementing these recommendations, PQR hopes to improve the performance of its PMO and thus increase the maturity of its project management in the future.